PENGARUH PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN: DAMPAK MODERASI DEWAN KOMISARIS - Titiek Puji Astuti; Nurul Herawati (Jurnal Akuntansi dan Pajak, 2022)
This study aimes to analyze how tax planning affects the firm value and the moderating effect of the board of commissioners on firm value. The study has the population regristered companies in Indonesia Stock Exhange in 2011-2016. The sampling technique uses purposive sampling method. The total observed data is 678 consist of 113 companies during six years observation. Data processing used regression analysis panel data by using software Eviews.The measurement of tax planning using (25%-ETR)*PBT. The result shows that tax planning has negative effect toward firm value and the moderating of the board of commissioners has effect on firm value Keywords : tax planning, firm value, the board of commissioners .